Peningkatan Kemampuan Guru dalam Pembuatan Media Pembelajaran Interaktif dengan Video Pembelajaran Berbasis Power Point melalui Kegiatan Pendampingan dan In House Training di SD Negeri 3 Ngareanak - Siti Solekhat (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
Learning in the digital era requires teachers to be able to use a variety of technology-based (IT) interactive learning media. Of course, besides being able to use media, teachers must also be able to create technology-based interactive learning media (IT) that are appropriate to the level of development of students. This is where the importance of the teacher's ability to create instructional media must always be improved. The creation of technology-based interactive learning media (IT) is closely related to the use of computers or laptops and various applications in them. One that is commonly used in classroom learning is Power Point media. Teachers can easily make Power Points, but for teachers who cannot operate computers or laptops at all, it is certainly very difficult. This is also the case at SD Negeri 3 Ngareanak, where most of the teachers are not proficient in operating computers or laptops. Of course, this is a problem that must be overcome using appropriate, effective and efficient steps. This research is a School Action Research (PTS) which consists of four stages, namely: (1) planning, (2) action, (3) observation, and (4) reflection and is carried out in 2 cycles with 3 meetings each cycle. The subjects of this study were teachers in grades I to VI at SD Negeri 3 Ngareanak, Singgorojo District, Kendal Regency, semester 2 of the 2022/2023 school year. There were 6 teachers at SD Negeri 3 Ngareanak, who were the subject of the study, consisting of 2 male teachers and 6 female teachers. The results of the study show that mentoring activities and In House Training which are carried out in a planned and sustainable manner can improve teachers' abilities in making interactive learning media with Power Point-based learning videos at SD Negeri 3 Ngareanak, Singgorojo District, Kendal Regency semester 2 of the 2022/2023 Academic Year. This is evident from the acquisition of the ability score in the initial conditions which was only 50.00 and then given action through mentoring and In House Training so that it increased to 68.52 in cycle I. Then in cycle II, the acquisition of the average teacher's ability score increased to 88, 43 and has successfully fulfilled the indicators of research success.